The Sub-Saharan Africa Challenge Program: An experiment in mainstreaming institutional learning and change - Acosta, A.S.; Jones, M.; Kaufmann, Ralph R. von (2005)
The Sub-Saharan Africa Challenge Program (SSA CP) shows how the principles of institutional learning and change (ILAC) can be applied. This Brief outlines the basic components of the SSA CP and highlights various ILAC features of the Program. These include an innovation systems orientation; an approach to ‘thinking globally and acting locally’; the location of research within a broader context of policy, market and institutional change; and an emphasis on collaboration and learning among program participants and with other agencies involved in agricultural research and development in Africa.